Peran Pemerintah Daerah Dalam Pengawasan Penanaman Modal Sektor Pariwisata (Studi Dinas Pariwisata Kabupaten Tapanuli Utara) - Juergen K. Marusaha. P. Panjaitan; Budiman Ginting; Mahmul Siregar; Rosnidar Sembiring (Universitas Sumatera Utara, 2019)
Abstract. The authority of the Regency / City Government in organizing investments in the field of tourism, Article 27 paragraph (1) of the Investment Law states that the Government coordinates investment policies, both coordination between Government agencies, between Government agencies and Bank Indonesia, between Government agencies and regional governments, as well as between regional governments, with delegation of authority from the central government to local governments. The role of districts / cities in controlling investment activities in the tourism sector, namely monitoring compilation, namely verification and evaluation of the Investment Activity Report (LKPM) and various other sources. Guidance by means of counseling on investment rules. Guidance is also carried out by providing investment consultations and guidance in accordance with the licensing provisions owned by investors. Implementation of investment supervision in the field of tourism at the North Tapanuli District Tourism Office, so far the North Tapanuli District Government has carried out oversight of investments in accordance with applicable regulations, but there are still several obstacles, namely the unavailability of how many PMA and PMDN companies are categorized as the planning stage , the development phase, and the commercial stage, the coordination function is still weak because the planning preparation process has not involved the investment / technical institutions in the Regency / City. Keywords: Supervision, Local Government, Investment, Tourism